2017
DOI: 10.3390/rs9111134
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rainfall Erosivity Estimates Using Merged TRMM and Gauge Data

Abstract: Soil erosion is a global issue that threatens food security and causes environmental degradation. Management of water erosion requires accurate estimates of the spatial and temporal variations in the erosive power of rainfall (erosivity). Rainfall erosivity can be estimated from rain gauge stations and satellites. However, the time series rainfall data that has a high temporal resolution are often unavailable in many areas of the world. Satellite remote sensing allows provision of the continuous gridded estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…The R factor in this study was calculated based on the merged daily rainfall data with rigorously quality control. Teng et al, (2017) demonstrated that the improved estimates of the R factor showed higher accuracy than the simple interpolated gauge-based approach. The K factor that we modelled in this study was based on the comprehensive soil properties and environment data sets currently available and geospatial methods.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The R factor in this study was calculated based on the merged daily rainfall data with rigorously quality control. Teng et al, (2017) demonstrated that the improved estimates of the R factor showed higher accuracy than the simple interpolated gauge-based approach. The K factor that we modelled in this study was based on the comprehensive soil properties and environment data sets currently available and geospatial methods.…”
Section: Discussionmentioning
confidence: 98%
“…We used rainfall estimates from the TRMM 3B42 Version 7, which have a spatial resolution of 0.25°×0.25° and a temporal resolution of 3 h (Ma et al, 2017). The R factor was calculated following the approach presented in Teng et al, (2017). Collocated cokriging (ColCOK) was used to merge the daily rainfall data that from the rain gauge stations and TRMM measurements to improve the quality of the precipitation data.…”
Section: Rusle Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To cover the whole and neighbouring area of TGRR, 69 stations were selected with a 60-kilometers buffer of the study area (Figure 3). The R factor was calculated following an approach widely used in China, for example by the National Water Conservancy Survey [27,28]:Ri=mj=1k(dji)n where R i is the R value of the half-month (MJ·mm·km −2 ·h −1 ); k is the number of days in the half-month i ; and d i j is the effective precipitation for day j (i.e., ≥12 mm) of the half-month i [29]. The parameters m and n were calculated as follows: m = 21.586 × n −7.1891 n = 0.8363 + 18.114/d 12 + 24.455/y 12 where d 12 is the average daily rainfall (≥12 mm), and y 12 is the yearly average rainfall for days with rainfall ≥12 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Segundo Hongfen et al (2017), os medidores de chuva fornecem informações valiosas sobre a quantidade e a frequência das chuvas, todavia a distribuição espacial desigual e as incoerências espaciais limitam a estimativa pluviométrica. Neste contexto, a utilização de dados de precipitação a partir de um satélite fornece uma solução alternativa para este problema, pois prop orcionam uma estimativa de precipitação espacialmente distribuída em grandes áreas.…”
Section: Fator Runclassified